Board Characteristics and ESG Performance: An Empirical Study of Public Companies in Indonesia - Pane, Josua Febrico Renaldo; Nainggolan, Yunieta Anny (Syntax Corporation, 2024)
This study examines the impact of board characteristics on the environmental, social, and governance (ESG) performance of publicly listed companies in Indonesia. Focusing on firms listed in the KOMPAS100 index, the research explores how board composition, including the number of directors and commissioners, gender diversity, independence, the presence of foreign members, and the sustainability committee, influences ESG scores. Using data from Sustainalytics, financial reports, and sustainability reports, the analysis includes control variables such as public shares, return on assets, leverage, firm age, firm size, and state ownership. Significant correlations were discovered between the characteristics of the board, the sustainability committee, and the ratings related to environmental, social, and governance factors (ESG). Companies that have larger boards, a higher proportion of female and independent directors, and international members exhibit superior environmental, social, and governance (ESG) performance. Sustainability committees contribute to the improvement of ESG outcomes. The findings indicate that implementing well-organized governance systems and having diverse board compositions are essential for successfully managing sustainability. The study utilized regression models to examine the influence of board features on ESG performance. Data from the KOMPAS100 index, which includes prominent Indonesian companies, was used for analysis. This empirical investigation offers useful insights into the ways in which corporate governance frameworks can influence sustainable business practices in the Indonesian context. Policymakers are advised to establish policies that encourage the formation of board diversity and sustainability committees. Corporate executives are recommended to optimize the composition of their boards in order to align with sustainability objectives, consequently enhancing environmental, social, and governance (ESG) performance and attaining competitive advantages.